Trabecular carcinoid tumor arising from a mature cystic teratoma - Chiu, Hsiao-Chen (Tzu Chi Med J, 2019)
Mature cystic teratomas (MCTs) are common benign tumors of the ovary. Coexistence of a carcinoid tumor inside an MCT is extremely rare. We present a 40-year-old woman who had intermittent abdominal pain and urinary frequency. An adnexal mass was detected during physical examination. Ultrasound indicated a 12.3 cm × 10.7 cm left ovarian mass. Surgical excision of the mass was performed, and histopathological examination revealed an MCT with three germ layers. The microcarcinoid tumor arising from an MCT showed a cord to trabecular pattern. The pathological diagnosis was a trabecular carcinoid tumor arising in an MCT. The patient did not present with carcinoid syndrome, and no recurrence was observed after 12 months of follow-up.